Central nervous system tumor registration in the Swedish Cancer Register and Inpatient Register between 1990 and 2014 - Tettamanti, Giorgio (Clin Epidemiol, 2019)
BACKGROUND: The Swedish Cancer Register (SCR) is characterized by excellent quality and completeness overall, but the quality of the reporting may vary according to tumor site and age, and may change over time. The aim of the current study was to investigate the completeness of the reporting of central nervous system (CNS) tumor cases to the SCR. MATERIALS AND METHODS: Individuals hospitalized for a CNS tumor between 1990 and 2014 were identified using the Inpatient Register; the proportion of identified cases that did not have any cancer diagnosis reported to the SCR was subsequently assessed. RESULTS: Between 1990 and 2014, 58,698 individuals were hospitalized for a CNS tumor, and a large proportion of them did not have any cancer diagnosis reported to the SCR (26%). This discrepancy was particularly pronounced for benign tumors and among elderly patients (over 30%). It was substantially lower for malignant brain tumors among adults (10%); moreover, no increase in the discrepancy between the two registers was observed in this group during the study period. Similar findings were found when assessing the concordance between the Cause of Death Register and the SCR. Among CNS tumor patients who were not reported to the SCR, a large proportion had only one hospital discharge diagnosis containing a CNS tumor (35%) and were less likely to be found in the Outpatient Register, which indicates that a large proportion of patients may have received an erroneous diagnosis. CONCLUSION: While a large proportion of CNS tumor patients were not reported to the SCR, the discrepancy between the SCR and the Inpatient Register was relatively small for malignant brain tumors among adults and has remained stable throughout the study period. We do not recommend that data from the Inpatient Register are combined with the SCR to estimate CNS tumor incidence, without proper confirmation of the diagnoses, as a considerable proportion of CNS tumor diagnoses registered in the Inpatient Register is unlikely to reflect true CNS tumors.